The psychological and social problems faced by foster family from social workers' perspective - Bin Sagar, Sarah Ibraihem; Al-Bardisi, Mardeyah (Journal of Humanities & Social Sciences, 2019)
This study is considered a quantitative research.The research aims to identify the most prominent psychological and social problems faced by foster family from the social workers' perspective to identify the role of social work in alleviating these problems.The study used the social survey methodology, the study tool was the questionnaire, and the study sample was purposive sample consisted of 31 social works who work with faster family in some social institutions in Riyadh.The main findings of the study include that the study sample agreed that foster families suffering in controlling the foster adolescence with an average (2.39 of 3) and standard deviation 0.615.Also, the sample study agreed that foster families faced difficulty in telling the foster child that he/she is adopted with a mean (2.58 of 3), and standard deviation of 0.502.There is a difference in the degree of approval of the study sample on the most important psychological problems experienced by foster families, where the rates of consent between (1.90 to 2.35).The study sample agree on the important role of social worker can play to reducing the foster families' social and psychological problems with an (2.97 of 3).
Keywords: alternative care; foster family; foster care; social problems; children of unknown parentage; psychological problems